Theoretical and Practical Analysis in Formulating Research Problems: A Literature Review - Nita Puspitawaty; Eva Hermala (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to identify key elements in the preparation of research problems, including characteristics, questions, sources, and research problem formulation techniques. This review uses a literature method by analyzing various articles and scientific books relevant to the topic, which are selected through strict inclusion criteria to ensure the quality and relevance of the data. The main findings suggest that a good research problem should have specific characteristics, such as relevance, clarity, and usefulness, which allow the research to contribute significantly in its field of science. The study also reveals that research questions should ideally be directed and testable, thus providing a solid basis for the formulation of research hypotheses and methodologies. In addition, the sources of research problems vary, including from empirical observations, previous literature, and theoretical gaps, which together enrich the context of the research. Effective problem formulation techniques involve an analytical and reflective approach, which takes into account problematic conditions in the literature, such as inconsistencies in findings or the need for a theory update. These findings are expected to be a reference for researchers in selecting and formulating research problems that have an impact and can encourage the quality and relevance of research in various disciplines.